A new catalyst CHCP-Fe2O3 for enhanced removal of tetracycline through the Fenton-like process: Economical synthesis, catalytic performance, and practicability. (February 2023) - He, Jiao; Pei, Baoyou; Deng, Chenglong; Huang, Dongha; Lv, Bihong; Peng, Cheng; Luo, Genggeng; Lin, JinQing
Abstract: Oxidation by the Fenton-like (Fe 3+ /H2 O2 ) process is considered an economically feasible technology for wastewater degradation, which relies heavily on the reactivity of the Fe2 O3 catalyst. In this study, a new catalyst C HCP -Fe 2 O 3 was fabricated by calcining an Fe-containing hyper-crosslinked polymer (HCP). The catalyst displayed outstanding catalytic performance (98.56 % removal rate and 57.96 % total organic carbon conversion efficiency) in the activation of H2 O2 for tetracycline degradation. By in situ impregnation, the Fe2 O3 in the catalyst can bond better with the carbon carrier, and the C HCP -Fe 2 O 3 -2 catalyst results in more structural defects and richer pores, which could supply more exposed reaction active sites and accelerate mass and electron transfer. This study demonstrates that the C HCP -Fe 2 O 3 /H 2 O 2 system exhibits excellent practical application potential because of its excellent recyclability and wide pH range (pH = 3–10) for the abatement of hazardous organic pollutants, which provides a facile and promising design of Fenton-like catalysts for wastewater treatment. Graphical abstract: Unlabelled Image Highlights: A catalyst was ingeniously fabricated by calcining FeCl3 -containing hyper-crosslinked polymer (HCP). The Fe2 O3 particles were homodisperse wrapped inside the carbon matrix, which was an ideal catalyst structure. The C HCP -Fe 2 O 3 -2 exhibited excellent recycle ability and wide pH operation range (pH = 3–10). The novel catalyst presented efficient TC abatement and TOC removal abilities. The C HCP -Fe 2 O 3 Fenton-like catalyst was inexpensive, efficient and stable for wastewater treatment.